The solar repair trade in Nairobi (Kenya): the blind spots of a “sustainable” electricity policy - Théo Baraille; Sylvy Jaglin (Territoire en Mouvement)
In Kenya and sub-Saharan Africa more broadly, decentralised solar electrification solutions hold out the promise of local development that both respects the environment and creates jobs. By examining the maintenance, repair, and recycling of photovoltaic solar equipment, this article compares these hopes to the actual impact of Kenya's solar policy on changes in a sector generally considered to provide local jobs, and with the potential to make a major environmental contribution to a resource-efficient circular economy conducive to recycling and reuse. It starts by showing that Kenya’s strategy of developing a dynamic solar market has had little impact on repair activities. First, because the industry’s dominant companies bypass the fundis (as technicians working in the pre-existing urban repair and recycling economy are called). And second, because repair is marginal to these companies’ business models. It then argues that repair services and know-how are being rendered obsolete by the increasing number of disposable microelectronic components in solar equipment, and looks at the environmental consequences of an industry producing increasing quantities of waste that is unsatisfactorily managed. In the light of these observations, it finally discusses the ambiguities of an electricity policy presented as conducive to a new relocalised green economy.